2021
DOI: 10.1177/15353702211047183
|View full text |Cite
|
Sign up to set email alerts
|

CTRP3 protects against uric acid-induced endothelial injury by inhibiting inflammation and oxidase stress in rats

Abstract: Hyperuricemia, which contributes to vascular endothelial damage, plays a key role in multiple cardiovascular diseases. This study was designed to investigate whether C1q/tumor necrosis factor (TNF)-related protein 3 (CTRP3) has a protective effect on endothelial damage induced by uric acid and its underlying mechanisms. Animal models of hyperuricemia were established in Sprague-Dawley (SD) rats through the consumption of 10% fructose water for 12 weeks. Then, the rats were given a single injection of Ad-CTRP3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…Sustained and excessive production of inflammatory cytokine and activation of inflammatory cells aggravate cisplatin-induced kidney damage ( Ozkok & Edelstein, 2014 ). According to our study findings, which were consistent with findings from a study suggesting that CTRP3 overexpression inhibited uric acid-induced inflammation with decreased levels of TNF-α and IL-6 ( Zhang et al, 2022 ), HK-2 cells exposed to cisplatin had lower levels of TNF-α and MCP-1 after treatment with CTRP3. Additionally, we found that CTRP3 overexpression alleviated the effects of cisplatin on the viability and apoptosis of HK-2 cells, consistently, the levels of apoptosis-related proteins Bcl-2 and Bax were reversed, whereas CTRP3 silencing aggravated these effects.…”
Section: Discussionsupporting
confidence: 92%
“…Sustained and excessive production of inflammatory cytokine and activation of inflammatory cells aggravate cisplatin-induced kidney damage ( Ozkok & Edelstein, 2014 ). According to our study findings, which were consistent with findings from a study suggesting that CTRP3 overexpression inhibited uric acid-induced inflammation with decreased levels of TNF-α and IL-6 ( Zhang et al, 2022 ), HK-2 cells exposed to cisplatin had lower levels of TNF-α and MCP-1 after treatment with CTRP3. Additionally, we found that CTRP3 overexpression alleviated the effects of cisplatin on the viability and apoptosis of HK-2 cells, consistently, the levels of apoptosis-related proteins Bcl-2 and Bax were reversed, whereas CTRP3 silencing aggravated these effects.…”
Section: Discussionsupporting
confidence: 92%
“…31 In addition, Zhang et al revealed that CTRP3 could ameliorate uric acid-stimulated inflammation in vascular endothelial cells. 32 Moreover, Meng et al proved that the CTRP3 content was obviously abridged in the hippocampus of mice with depression, and CTRP3 curbed inflammatory response in depressive mouse model by modulating NF-κB signaling. 33 In addition, CTRP3 participates in the regulation of obesity, metabolic dysfunction, and cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Incremental CTRP3 increased the expression of p-PI3K, p-Akt and p-eNOS, indicating that CTRP3 facilitated the activation of PI3K/Akt/eNOS pathway (47). CTRP3 ameliorated uric acid-induced endothelial inflammation and oxidative stress, possibly by inhibiting TLR4-mediated inflammation and down-regulating oxidative stress (81). Globular form CTRP5 is a novel molecule that leads to vascular EC dysfunction through Nox1-mediated mitochondrial apoptosis in diabetes, which indicates that interventions blocking gCTRP5 may protect diabetic EC function (82).…”
Section: Ctrp3 Ctrp5 and Ctrp6mentioning
confidence: 95%